2005
DOI: 10.1007/s11664-005-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical activation studies of Si-implanted GaN

Abstract: Comprehensive and systematic electrical and optical activation studies of Siimplanted GaN were made as a function of ion dose and anneal temperature. Silicon ions were implanted at 200 keV with doses ranging from 1 ϫ 10 13 cm Ϫ2 to 5 ϫ 10 15 cm Ϫ2 at room temperature. The samples were proximity-cap annealed from 1050°C to 1350°C with a 500-Å-thick AlN cap in a nitrogen environment. The optimum anneal temperature for high dose implanted samples is approximately 1350°C, exhibiting nearly 100% electrical activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The lack of electrical activation after annealing at 1150°C is also apparent in the mobility data for the samples implanted with the lowest Si dose of 1 9 10 14 cm À2 , showing only 21 cm 2 /V s. This mobility value is lower than those for the higherdose-implanted samples, and also those measured for GaN and Al x Ga 1Àx N with lower Al mole fraction. [3][4][5]19 This indicates that this annealing temperature is too low to sufficiently activate implanted ions and/or to repair lattice damage during annealing. However, the samples for this lowest dose of 1 9 10 14 cm À2 show much higher mobilities than the other high-dose samples after annealing at 1200°C or higher because both impurity and defect scattering are less for this dose due to the relatively smaller number of impurities and the smaller amount of residual damage.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of electrical activation after annealing at 1150°C is also apparent in the mobility data for the samples implanted with the lowest Si dose of 1 9 10 14 cm À2 , showing only 21 cm 2 /V s. This mobility value is lower than those for the higherdose-implanted samples, and also those measured for GaN and Al x Ga 1Àx N with lower Al mole fraction. [3][4][5]19 This indicates that this annealing temperature is too low to sufficiently activate implanted ions and/or to repair lattice damage during annealing. However, the samples for this lowest dose of 1 9 10 14 cm À2 show much higher mobilities than the other high-dose samples after annealing at 1200°C or higher because both impurity and defect scattering are less for this dose due to the relatively smaller number of impurities and the smaller amount of residual damage.…”
Section: Resultsmentioning
confidence: 99%
“…However, in order to make the implanted ions optically and electrically active, it is required to anneal out the implantation damage-related defects without dissociation of host atoms. Previous studies have shown that the activation of implanted impurities in III-nitride materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] is much more difficult than for conventional compound semiconductors such as GaAs and InP. A number of articles 1-8 and reviews 9-10 reporting on ion implantation studies in GaN have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al 6 reported electrical activation efficiency as high as 90% for GaN implanted with 100 keV Si ions at a dose of 5 3 10 15 cm ÿ2 and annealed at 1,400°C for 10 sec. Fellows et al 7,8 reported a 100% electrical activation for GaN implanted with Si at high doses (!1 3 10 15 cm ÿ2 ) and annealed at 1,350°C. However, they reported lower activation efficiencies for low dose ( 5 3 10 14 cm ÿ2 ) implanted samples, and efficiencies increased with anneal temperature even after annealing at 1,350°C.…”
Section: Introductionmentioning
confidence: 99%
“…Also, H-, He-, or N-ion implantation has been used in device isolation to compensate effectively both p-and ntype GaN [1][2][3][4]. Although significant progress has been reported for ion implantation doping and annealing of GaN and AlGaN, there are still many areas to be further investigated [5][6][7][8][9]. Implantation damage created in III-nitrides is very difficult to remove, making it hard to electrically activate the implanted ions.…”
mentioning
confidence: 99%
“…Implantation damage created in III-nitrides is very difficult to remove, making it hard to electrically activate the implanted ions. Most of the reported studies have indicated that an anneal temperature of 1200 o C or higher for short anneal time periods is required to repair the damage from implantation [5][6][7][8]. Cao et al [5] , respectively, after annealing at 1350 o C for 2 min.…”
mentioning
confidence: 99%